2011
DOI: 10.1093/nar/gkr705
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of bamboo mosaic virus satellite RNA (satBaMV)-encoded protein P20 downregulates the formation of satBaMV-P20 ribonucleoprotein complex

Abstract: Bamboo mosaic virus (BaMV) satellite RNA (satBaMV) depends on BaMV for its replication and encapsidation. SatBaMV-encoded P20 protein is an RNA-binding protein that facilitates satBaMV systemic movement in co-infected plants. Here, we examined phosphorylation of P20 and its regulatory functions. Recombinant P20 (rP20) was phosphorylated by host cellular kinase(s) in vitro, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and mutational analyses revealed Ser-11 as the phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
0
28
1
Order By: Relevance
“…The P20 Protein Plays a Crucial Role in SatBaMV Systemic Movement in N. benthamiana Previously, we showed that the trafficking of P20-defective satBaMV exhibits low efficiency in N. benthamiana coinfected with BaMV HV (Lin et al, 1996;Vijaya Palani et al, 2006;Vijayapalani et al, 2012). To provide further insights into the role of P20 in the systemic movement of satBaMV, we generated transgenic N. benthamiana expressing the P20 protein under the phloem companion cell-specific SUC2 promoter ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The P20 Protein Plays a Crucial Role in SatBaMV Systemic Movement in N. benthamiana Previously, we showed that the trafficking of P20-defective satBaMV exhibits low efficiency in N. benthamiana coinfected with BaMV HV (Lin et al, 1996;Vijaya Palani et al, 2006;Vijayapalani et al, 2012). To provide further insights into the role of P20 in the systemic movement of satBaMV, we generated transgenic N. benthamiana expressing the P20 protein under the phloem companion cell-specific SUC2 promoter ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike most satRNA-encoded proteins required for satRNA replication (Hu et al, 2009), the satBaMV-encoded P20 nonstructural protein assists satBaMV long-distance trafficking in plants (Lin et al, 1996;Vijaya Palani et al, 2006;Vijayapalani et al, 2012) (Figure 1). Previously, we showed that P20 can preferentially bind to the 59-and 39-untranslated regions of satBaMV to form satBaMV-P20 RNP complexes (Tsai et al, 1999;Vijayapalani et al, 2012) and that formation of the complexes is negatively regulated by P20 phosphorylation (Vijayapalani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations